Sustainable corrosion protection of steel bulkhead wall by installation of pultruded GFRP panels - Hachem, Ghassan; Raphael, Wassim (Edelweiss Applied Science and Technology, 2025)
In marine environments, particularly in wharf structures, the corrosion of steel bulkhead walls poses a significant threat to structural integrity and safety, resulting in substantial economic and environmental burdens due to frequent maintenance and potential structural failures. Traditional corrosion protection methods, such as coatings and cathodic protection, offer temporary solutions but are hindered by their limited lifespan, high maintenance costs, and potential environmental impacts due to the use of hazardous materials. This study proposes a solution utilizing pultruded Glass Fiber Reinforced Polymer (GFRP) panels in conjunction with concrete fill to provide sustainable and effective corrosion protection for steel bulkhead walls in wharfs. The pultrusion process ensures the production of high-quality GFRP panels with consistent properties, making them an ideal material for marine applications. These panels act as a waterproof membrane, preventing direct contact between the steel structure and corrosive seawater. The concrete fill not only provides structural support but also acts as a corrosion inhibitor by maintaining a high pH environment, which passivates the steel surface, forming a protective oxide layer that suppresses corrosion reactions. A corrosion protection project was completed using this technique at ATCL marina in Lebanon, offering a promising alternative to traditional methods, such as painting. This case study contributes to the advancement of corrosion protection technologies, addressing the critical need for durable, environmentally friendly solutions in marine infrastructure and paving the way for future innovations in marine structural protection.